Neotropical Piper species: Are they all hermaphroditic? - Valentin-Silva, Adriano [UNESP] (2018)
Sexual expression has been used as a distinctive character among the clades of the genus Piper. Unisexual flowers are described for Paleotropical species, which are usually dioecious, whereas bisexual flowers are associated with Neotropical species, considered as hermaphroditic. However, the registration of an andromonoecious species in the Neotropics, associated with the morphological similarity of Piper flowers, suggests that the presence of functionally unisexual flowers may be more common than the one recorded so far. To investigate this possibility, we determined the sexual expression of 17 Neotropical Piper species, focusing on the functionality of the flowers along the anthesis in individuals of a semideciduous seasonal forest. We found 13 hermaphroditic species, one andromonoecious and three with variable combinations of hermaphroditic, andromonoecious and male individuals. The staminate flowers presented cryptic unisexuality. Species with more than one floral type presented sexual dimorphism, differing in length of their inflorescences and pistils of flowers. Although hermaphroditism is the predominant sexual expression among Neotropical Piper species, we observed variations of this expression in almost 25% of the species studied here, indicating that the unisexual flowers may have evolved independently in different clades of Neotropical and Paleotropical species.